2013
DOI: 10.1371/journal.pone.0065057
|View full text |Cite
|
Sign up to set email alerts
|

Fishers’ Behaviour in Response to the Implementation of a Marine Protected Area

Abstract: Marine Protected Areas (MPAs) have been widely proposed as a fisheries management tool in addition to their conservation purposes. Despite this, few studies have satisfactorily assessed the dynamics of fishers’ adaptations to the loss of fishing grounds. Here we used data from before, during and after the implementation of the management plan of a temperate Atlantic multiple-use MPA to examine the factors affecting the spatial and temporal distribution of different gears used by the artisanal fishing fleet. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 39 publications
0
29
0
1
Order By: Relevance
“…Further, the relative continuity of habitat across reserve boundaries can also impact fishing effort (see e.g., Freeman et al 2009;Huserbråten et al, 2013, Kay, Lenihan, Kotchen, & Miller, 2012. Similarly, Horta e Costa et al (2013) showed how different fisheries and gear types respond differently to a midlatitude MPA where some fished a broader area and others kept preferred territories.…”
Section: Introductionmentioning
confidence: 96%
“…Further, the relative continuity of habitat across reserve boundaries can also impact fishing effort (see e.g., Freeman et al 2009;Huserbråten et al, 2013, Kay, Lenihan, Kotchen, & Miller, 2012. Similarly, Horta e Costa et al (2013) showed how different fisheries and gear types respond differently to a midlatitude MPA where some fished a broader area and others kept preferred territories.…”
Section: Introductionmentioning
confidence: 96%
“…; Horta e Costa et al . ). More generally, MPAs are increasingly used as a tool for fishery management (Rocklin et al .…”
Section: Introductionmentioning
confidence: 97%
“…Understanding the interactions between large MPAs and marine fisheries could significantly advance our comprehension of MPA effectiveness as a conservation and management tool (Horta e Costa et al 2013, Stevenson et al 2013). On one hand, MPAs that disallow fishing might simply displace effort to other areas that may then be subject to overfishing (Halpern et al 2004).…”
Section: Open Pen Access Ccessmentioning
confidence: 99%